The importance of nurses in cognitive and memory stimulation in the elderly: an integrative review (Research, Society and Development, 2020)
It is an integrative review with a quantitative approach, whose objective is to analyze scientific productions about the role of nurses in cognitive and memory stimulation in elderly people, based on the articles collected in the online databases. Nine publications found in the national scientific databases Lilacs, Medline, BDENF, PUBMED and SCOPUS were selected for the study. The descriptors used were: Cognition; Nursing; Old man; Memory. In the discussion were addressed: The cognitive and memory stimulus in an elderly person without Diagnosis of Dementia Syndromes and the cognitive and memory stimulus in an elderly person with Diagnosis of Dementia Syndromes. It is concluded that the importance of the nurse in the cognitive and memory stimulation of the elderly is crucial for the quality of life of the elderly population, seeking new strategies and technologies for the maintenance of cognitive intelligence and memory in healthy elderly people and delaying the progress of dementia syndromes, especially Alzheimer's disease.